Life cycle assessment of agre-food systems An operational guide dedicated to developing and emerging economies - Basset-Mens, Claudine; Avadí, Angel; Bessou, Cécile; Acosta-Alba, Ivonne; Biard, Yannick; Payen, Sandra (éditions Quae, 2021)
Life Cycle Assessment (LCA) is the internationally recognized method to assess the environmental impacts of products and services. Its application to agri-food systems in developing or emerging contexts is recent and represents many challenges of scientific, partnerial and operational nature. With more than 10 years of scientific and field experience, the CIRAD LCA team has synthesized, with other internationally recognized experts, the best knowledge and approaches available to apply LCA under these conditions. This operational guide is a useful tool for LCA practitioners; it provides best practice recommendations to carry out LCA studies on agri-food products in developing and emerging contexts.